Rupture Risk Assessment for Mirror Aneurysms with Different Outcomes in the Same Patient - Tian, Zhongbin; Zhang, Yisen; Jing, Linkai; Liu, Jian; Zhang, Ying; Yang, Xinjian (Frontiers in Neurology, 2016)
Background: The purpose of this research was to analyze the effect of morphologic and hemodynamic characteristics on mirror aneurysms in which one ruptured and the other did not, within the same patient, and to identify reliable predictors of rupture. Methods: We performed three-dimensional angiographic imaging in 56 patients with intracranial mirror aneurysms for computational fluid dynamic studies from January 2009 to December 2015. The ruptured aneurysm simulations were conducted with geometry obtained after rupture. The significance of morphologic and hemodynamic parameters with respect to rupture was analyzed. Multivariate logistic regression analysis was applied to significant parameters to identify independent discriminators. Results: Three morphologic factors (aneurysm size, aspect ratio, and size ratio) and two hemodynamic factors (time-averaged mean wall shear stress [WSS] and low WSS area [LSA]) were statistically associated with aneurysm rupture (p<0.05). On multivariate logistic regression, a larger size (OR 2.572, p=0.001) and lower WSS (OR 0.609, p=0.045) were independent significant factors for rupture. Conclusions: Larger aneurysm size and lower WSS were independently associated with the rupture status of aneurysms. These findings need to be confirmed by large multicenter and multipopulation studies.